ANALISIS KINERJA KEUANGAN PT KINO INDONESIA SEBELUM DAN SESUDAH PANDEMI COVID 19 - Fitria, Nita; Asril, Yona (Jurnal Akuntansi Syariah (JAkSya), 2024)
The purpose of this research is to analyze and determine the financial performance of PT Kino Indonesia Tbk for the 2018-2022 period in terms of liquidity, solvency, activity and profitability ratios. Data collection was carried out by accessing the official website of the Indonesian Stock Exchange, namely: www.idx.co.id. The research results show that the financial performance of PT Kino Indonesia Tbk in terms of liquidity ratios seen from the current ratio, quick ratio and cash ratio in 2019-2020 and 2022 is in poor condition. The solvency ratio seen from DAR, DER and TATD in 2019-2020 and 2022 is in poor condition. Judging from the 2019-2022 LTDER, it is in poor condition. Judging from the 2019 TADC, it is in poor condition. The activity ratio seen from the WCTO 2021-2022 is in poor condition. Judging from TATO, 2019-2021 is not good. Judging from the ITO in 2020 and 2022, it is in poor condition. Judging from the 2019-2022 FATO and RTO, it is in poor condition. The profitability ratio is seen from NPM, ROA, ROE and ROS in 2019 compared to 2018 in good condition, 2020-2022 in less good condition. Judging from the GPM in 2019-2020 it is in good condition and in 2021-2022 it is in poor condition